2018
DOI: 10.15560/14.5.763
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of the genus Riccia L. (Marchantiales, Ricciaceae) in Maranhão state, Brazil

Abstract: Ricciaceae is a little-known liverwort family in northeastern Brazil. Fieldwork in 4 localities in Maranhão state yielded 4 species of Riccia, with 2 taxa, R. mauryana and R. weinionis, representing new state records. This paper describes the species diversity of the genus Riccia in Maranhão state, and provides descriptions, ecological notes, and illustrations for each species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…In our study area, we found seven species of thalloid liverworts, which are distributed in six genera and six families. These seven species represent 16% of the thalloid liverwort species in northeastern Brazil, a 57% increase in the number of thallose species known from Maranhão state (Silva et al 2018; Flora do Brasil 2020). Most of the species found in our study are Neotropical in distribution, but Cyathodium cavernarum Kunze has a pantropical distribution (Gradstein and Costa 2003;Bischler-Causse et al 2005; Söderström et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study area, we found seven species of thalloid liverworts, which are distributed in six genera and six families. These seven species represent 16% of the thalloid liverwort species in northeastern Brazil, a 57% increase in the number of thallose species known from Maranhão state (Silva et al 2018; Flora do Brasil 2020). Most of the species found in our study are Neotropical in distribution, but Cyathodium cavernarum Kunze has a pantropical distribution (Gradstein and Costa 2003;Bischler-Causse et al 2005; Söderström et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, R. vitalii can be easily distinguished from R. weinionis by the form and ornamentation of the spores. In R. vitalii, the spores are subspherical to subtetrahedral, with a granular proximal face and an evident trilete mark, whereas in R. weinionis the spores are tetrahedral with a proximal face with few areolas and without a trilete mark (Silva et al 2018). Distribution and ecology.…”
Section: Riccia Stenophylla Sprucementioning
confidence: 99%
See 2 more Smart Citations
“…;Nascimento et al, 2018b. ;Nascimento et al, 2019;Nascimento et al, 2020;Oliveira et al, 2018;Salazar-Ferreira et al, 2020;Silva et al, 2016;Silva et al, 2018a;Silva et al, 2018b. ;Silva-Moraes et al, 2019).…”
Section: Discussionunclassified